Effects of turmeric curcuminoids and metformin against central sensitivity to pain in mice - Verma, Suruchi (J Tradit Complement Med, 2016)
The reported experimental study was conducted to compare the effects of repeated daily oral doses of curcuminoids (CLE) with metformin as potential antidepressants and analgesics. Effects of a single and ten daily oral doses of CLE (5, 20, 80 mg/kg/day) and of 50 mg/kg/day metformin (MET) were compared in mice hot plate test (HPT) for analgesics. On the 11th treatment day, all animals were subjected to foot shock stress triggered hyperthermia test, and on the 12th treatment day to tail suspension test (TST) for antidepressants. Immediately thereafter, their blood levels of glucose, insulin and cortisol were quantified. Dose dependent analgesic activity of CLE was observed in HPT, whereas the metformin dose tested suppressed only pain hypersensitivity in the test. But statistically significant effects of both of them were observed in TST, and both of them also afforded protections against body weight loss and slight elevation in core temperatures induced by daily handling and repeated testing. CLE or metformin had no significant effects in foot shock stress triggered transient hyperthermic responses or on blood glucose, insulin and cortisol levels. Reported results reveal that curcuminoids as well as metformin are stress response modifiers with antidepressants like activities, but only low dose curcuminoids possess centrally acting analgesics like activities. They suggest that the bio-assay system used in this study is well suited for identifying curcuminoids like plant metabolites with analgesic and anti-stress activities, and that low dose curcuminoids are more effective as analgesics than low dose metformin.